Assessment of the risk of burnout and its associated factors in healthcare professionals during the COVID-19 pandemic: A prospective cohort study - Silva, Rebeca R. C.; Menezes, Rodrigo C.; Garcia, Stefania L.; Pustilnik, Hugo N.; Ferreira, Isabella B. B.; Aguiar, Kaique V. C. S.; Filgueiras Filho, Nivaldo M.; Araújo-Pereira, Mariana; Andrade, Bruno B. (Frontiers in Psychology, 2023)
Introduction: The COVID-19 pandemic resulted in tremendous physical and psychological pressure on healthcare professionals, especially on those working in intensive care units (ICUs) and Emergency Departments (EDs). The present study intended to characterize the profile of these professionals which is associated with burnout and determine the potential predictors of such condition. Methods: A Prospective cohort study was carried out in a tertiary hospital between March 2020 and March 2021, in Salvador, Brazil. A standardized and validated version of the Oldenburg Burnout inventory (OLBI) was applied to assess risk of burnout together with data forms designed to collect information on sociodemographic characteristics and religious beliefs. ICU and ED healthcare professionals were evaluated during off-hours at two distinct periods of the COVID-19 pandemic, in 2020 and in 2021. Differences in the results obtained from each study participant between the timepoints were compared. A binary logistic regression analysis was performed to identify the predictors of burnout development independent of other confounding factors. Results: 77 healthcare professionals with a median age of 33 (interquartile range [IQR]: 31 – 37.5) years and predominantly female (72.7%; n=56) were enrolled. There were 62 professionals at risk of developing burnout through the OLBI. Those had a median age of 33 (IQR: 31-37) and female predominance (71%, n=44). Disengagement and burnout were the only features which frequencies significantly changed over time, with increasing detection at the latest timepoint. Alcohol consumption was found to be an important risk factor for burnout development (adjusted odds ratio [aOR]: 10.8 [95% CI: 1.8–64.2]). Importantly, working in the ICU (aOR: 0.04 [95%CI: 0.01–0.32)] and the habit of praying daily (aOR: 0.07 [95%CI: 0.01–0.41]) were characteristics linked to reduced odds of burnout. Discussion: Disengagement substantially increased during the COVID-19 pandemic in healthcare professionals. Alcohol consumption favors the onset of burnout whereas habit of praying daily and working in the ICU are protective against such outcome. Institutional policies aimed at minimizing etilism may positively impact mental health of these professionals.